Uzbekistan Energy Efficiency in Urban Water Utilities in Central Asia - Ijjaz-Vasquez, Ede Jorge (World Bank, Washington, DC, 2014)
This study's objective was to evaluate Energy Efficiency in Urban Water Utilities to test the common assumption that there existed an enormous energy reduction potential in the water utilities in the Former Soviet Union and more specifically in Central Asia. The study focused on the historic cities of Samarkand and Bukhara in Uzbekistan and includes a detailed description of the water supply and distribution facilities, the conditions of the works identifying low energy efficiency, a detailed analysis of the efficiency tests performed to pumps of the Water Utilities in these cities, an energy usage assessment including the performance indicators, and investment recommendations and a dissemination program incorporating final recommendations to reduce energy consumption by the cities water systems.